Taking sides : clashing views on controversial issues in human sexuality - Francoeur, Robert T (Dushkin Publishing Group, 1994)
This debate-style reader is designed to introduce students to controversies in human sexuality. The readings, which represent the arguments of leading social commentators, educators, and sexologists, reflect a variety of viewpoints and are staged as \"pro\" and \"con\" debates. Issues debated include biology, behavior and human sexuality, issues in reproduction and health, and legal and social issues.
Keywords: sexuologie; sexualita; Sexuality